Buckling due to external pressure of a composite tube measured by Rayleigh optical backscatter reflectometry and analyzed by finite elements. Issue 8 (30th May 2018) - Hugaas, Eivind; Vedvik, Nils Petter; Echtermeyer, Andreas T.
Summary: There is a growing interest in replacing steel tubes that operate in high pressure and high temperature environments with composite tubes. Such applications can include drilling risers and drill strings for the offshore oil industry. Replacing steel with composites in such applications will greatly reduce the weight of the equipment and require less buoyancy elements built into the structures. This paper seeks to investigate how composite tubes behave when submerged and how optical fibers can be used as a health monitoring system for such applications utilizing Rayleigh optical backscatter reflectometry. A glass fiber filament wound tube of 100 mm inner diameter and 600 mm length with a layup of approximately [89 °,  ±12.7 °,  ±45 ° ] was exposed to external hydrostatic pressure in an autoclave. Optical fibers glued to the outer surface of the tube were used to measure strain during testing. A strain field reading was carried out every 0.5 bar pressure increase and correlated well with strain fields from a finite element analysis of the tube. The finite element analysis predicted buckling at 4.33 bar, assuming no material failure; however, the tube buckled at 3.5 bar due to a sudden stiffness reduction from material failure. The optical fibers could detect the early failure and functioned well as a health monitoring system.